2007
DOI: 10.1111/j.1439-0418.2007.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of resistance to tebufenozide in field populations of Cydia pomonella L.: methods and mechanisms

Abstract: Four populations of codling moth Cydia pomonella L. were collected as overwintering larvae from apple orchards with different pesticide pressure (S. Michele, Roncafort, Revo`and Vervo`) in the Trento province (northern Italy). Mortality rate caused by a predetermined discriminating concentration of tebufenozide topically applied on overwintering larvae was evaluated. Neonate F1 progeny of the same populations were assayed for susceptibility to tebufenozide by feeding them on thinning apples treated with an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 34 publications
(83 reference statements)
4
31
0
1
Order By: Relevance
“…The dose response laboratory bioassays showed that emamectin benzoate had a similar high level of intrinsic toxicity to early‐stage larvae of both C. pomonella and C. molesta . In a previous experiment, Ioriatti et al 5 used the same C. pomonella culture and laboratory bioassay, which resulted in LC 50 values for the MAC tebufenozide 10 times higher than those found in this study for emamectin benzoate. Moreover, emamectin benzoate has been reported to be the most active compound against Grapholitha lobarzewskii Nowicki, with an LC 50 of 0.01 mg L −1 17…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The dose response laboratory bioassays showed that emamectin benzoate had a similar high level of intrinsic toxicity to early‐stage larvae of both C. pomonella and C. molesta . In a previous experiment, Ioriatti et al 5 used the same C. pomonella culture and laboratory bioassay, which resulted in LC 50 values for the MAC tebufenozide 10 times higher than those found in this study for emamectin benzoate. Moreover, emamectin benzoate has been reported to be the most active compound against Grapholitha lobarzewskii Nowicki, with an LC 50 of 0.01 mg L −1 17…”
Section: Discussionmentioning
confidence: 50%
“…The efficacy of C. pomonella control is threatened by the widespread development of resistance to pesticides 3. Resistance to different classes of insecticides has recently been documented in codling moth populations by using topical applications on overwintering larvae, a sensitive technique for detecting resistance 4, 5. According to Charmillot et al ,6, 7 the only insecticide to which resistance has not developed is emamectin benzoate, which has been shown to be highly effective in laboratory tests on populations resistant to diflubenzuron and tebufenozide.…”
Section: Introductionmentioning
confidence: 99%
“…Codling moth evolved resistance to lead arsenate in the early twentieth century7 and to DDT in the early 1950s,8 and it has since developed resistance to virtually every insecticide group. On a worldwide scale, populations have developed resistance to organophosphates,9–13 to benzoylureas including diflubenzuron,14–18 to the diacylhydrazines (tebufenozide and methoxyfenozide19, 20) and to pyrethroids 17, 20, 21. The occurrence of populations resistant to insecticides shortly after their appearance on the market in both Europe3 and the United States20 suggests that cross‐resistance is a potential concern for new classes of chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Topical applications to fully developed post‐diapause larvae were used to monitor for diflubenzuron17, 18 and tebufenozide19 resistance in field populations, and diagnostic doses were proposed for a diversity of insecticides 18. This bioassay required the collection of diapausing larvae in corrugated cardboard strips placed around the tree trunk, and then exposing the larvae to cold treatment for a minimum of 3 months to complete diapause development.…”
Section: Introductionmentioning
confidence: 99%
“…O uso repetitivo de inseticidas no mesmo ciclo vegetativo pode selecionar populações resistentes (SAUPHANOR et al, 1998;IORIATTI et al, 2007), comprometendo a eficiência do controle.…”
Section: Introductionunclassified